Composite conductive agent, method for preparing the same, and solid-state battery
Patent Information
- Application Number
- CN202510976404.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-15
AI Technical Summary
[0004]有鉴于此,本发明致力于提供一种复合导电剂及其制备方法和固态电池,以解决现有技术中的导电剂容易导致硫化物电解质降解的问题
[0060]本发明所提供的复合导电剂,可以应用在固态电池中,尤其是可以应用在含有硫化物固态电解质的固态电池中。该复合导电剂由内至外依次包括导电剂、第一包覆层和第二包覆层,其中的第一包覆层包括第一金属,第二包覆层包括第二金属,第一金属的还原性比第二金属强。这样,在不影响正极电子运输的情况下,通过在导电剂的表面包覆两层金属层,其中,内层为第一金属包覆层,外层为第二金属包覆层,第一金属的还原性强于第二金属,进而还原性较强的第一金属包覆层优先与固态电解质(如硫化物固态电解质,Li6PS5Cl)反应生成稳定界面相(如MgS、ZnS),抑制硫化物分解。外层为第二金属包覆层,其中的第二金属具有高导电性以及化学惰性,可保障电子快速传输,同时第二金属的化学惰性抑制与电解质的持续反应。进而,该复合导电剂通过第一包覆层和第二包覆层的不同作用机制极大地抑制了导电剂引起的硫化物电解质分解,提高了硫化物电池的电化学性能。
Smart Images

Figure CN121035208B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, and more specifically, to a composite conductive agent, its preparation method, and a solid-state battery. Background Technology
[0002] Sulfide solid electrolytes possess the highest room-temperature ionic conductivity among solid-state lithium-ion conductors to date, thus attracting increasing attention in high-energy-density and high-safety all-solid-state batteries. To achieve the high energy density of sulfide solid-state batteries, maximizing the utilization of the active material in the cathode is essential. It is well known that carbon-based conductive additives can improve the capacity and rate performance of composite electrode materials. However, the limited electronic conductivity in the active material significantly restricts electron transport capabilities. Active materials are typically spherical, resulting in a small electron contact area between particles in the cathode composite material. To overcome this limitation, adding appropriate amounts of carbon-based conductive additives has a significant effect on improving the electron permeation network. Recent studies show that carbon-based conductive additives often lead to accelerated capacity loss during cycling and accelerate the formation of decomposition products in the solid electrolyte, especially in all-solid-state batteries with high-nickel cathodes matched with sulfide solid electrolytes. Currently, the main method to reduce the degree of solid electrolyte decomposition is to use carbon-based conductive additives with small surface areas and fibrous morphology. However, this strategy is only effective in the early stages of battery operation. As the operating time increases, the side reactions become more and more serious, which is not conducive to the preparation of all-solid-state batteries with long lifespan.
[0003] Therefore, overcoming the degradation of sulfide electrolytes caused by the use of carbon-based conductive additives, reducing long-term battery capacity decay, and improving the overall performance of batteries are urgent problems to be solved. Summary of the Invention
[0004] In view of this, the present invention aims to provide a composite conductive agent, its preparation method and a solid-state battery, so as to solve the problem that conductive agents in the prior art are prone to causing degradation of sulfide electrolytes.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows:
[0006] This invention provides a composite conductive agent, the composite conductive agent comprising a conductive agent, a first coating layer covering at least a portion of the surface of the conductive agent, and a second coating layer covering at least a portion of the surface of the first coating layer;
[0007] The material of the first coating layer includes a first metal, and the material of the second coating layer includes a second metal;
[0008] The reducing power of the first metal is stronger than that of the second metal.
[0009] In some specific embodiments, the first metal includes at least one of Group IIA, Group IIB or Group IIIA metals.
[0010] In some specific embodiments, the second metal includes at least one of Group IB metals.
[0011] In some specific embodiments, the first metal includes at least one of Mg, Zn, Al, and Ca.
[0012] In some specific embodiments, the second metal includes Ag and / or Cu.
[0013] In some specific embodiments, the first coating layer completely covers the surface of the conductive agent.
[0014] In some specific embodiments, the second covering layer completely covers the surface of the first covering layer.
[0015] In some specific embodiments, the thickness of the first coating layer is greater than the thickness of the second coating layer.
[0016] In some specific embodiments, the thickness of the first coating layer is 5 nm to 8 nm.
[0017] In some specific embodiments, the thickness of the second coating layer is 3nm to 5nm.
[0018] In some specific embodiments, the conductive agent includes a carbon-based conductive agent.
[0019] In some specific embodiments, the carbon-based conductive agent includes at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0020] In some specific embodiments, the specific surface area of the carbon fiber is 15 m². 2 / g~25m 2 / g.
[0021] A second aspect of the present invention also provides a method for preparing a composite conductive agent, comprising the following steps:
[0022] Using a conductive agent as a substrate, a first metal precursor is deposited on the surface of the conductive agent by atomic layer deposition. A first reducing agent is introduced to react with the first metal precursor to form a first coating layer on the surface of the conductive agent.
[0023] Then, a second metal precursor is deposited on the surface of the first coating layer by atomic layer deposition. A second reducing agent is introduced to react with the second metal precursor to form a second coating layer on the surface of the first coating layer, thereby obtaining the composite conductive agent.
[0024] The reducing power of the first metal in the first metal precursor is stronger than that of the second metal in the second metal precursor.
[0025] In some specific embodiments, the specific process of forming the first coating layer includes:
[0026] The conductive agent is placed in an atomic layer deposition apparatus, and a first carrier gas and a first metal precursor are introduced to perform a first vapor phase deposition on the surface of the conductive agent. Then, a first reducing agent is introduced to perform a first reaction with the first metal precursor.
[0027] Repeat the above process to form the first coating layer of the target thickness on the surface of the conductive agent.
[0028] In some specific embodiments, the process of forming the second coating layer includes:
[0029] A second carrier gas and a second metal precursor are introduced into an atomic layer deposition apparatus to perform a second vapor phase deposition on the surface of the conductive agent coated with a first coating layer. Then, a second reducing agent is introduced to react with the second metal precursor in a second reaction.
[0030] Repeat the above process to form a second coating layer of the target thickness on the surface of the first coating layer.
[0031] In some specific embodiments, the temperature of the first vapor deposition is 120°C to 280°C; the time of the first vapor deposition is 3s to 6s; and the pressure of the first vapor deposition is 10... -4 MPa ~ 10 -3 MPa.
[0032] In some specific embodiments, the first carrier gas includes at least one of nitrogen, argon, helium, or neon.
[0033] In some specific embodiments, the first metal precursor includes one of a magnesium-containing compound, a zinc-containing compound, an aluminum-containing compound, or a calcium-containing compound.
[0034] In some specific embodiments, the magnesium-containing compound includes cyclopentadienyl magnesium and / or methylcyclopentadienyl magnesium.
[0035] In some specific embodiments, the zinc-containing compound includes diethylzinc and / or zinc acetylacetonate.
[0036] In some specific embodiments, the aluminum-containing compound includes at least one of trimethylaluminum, isobutylaluminum, triethylaluminum, or aluminum chloride.
[0037] In some specific embodiments, the calcium-containing compound includes cyclopentadienyl calcium and / or tert-butoxy calcium.
[0038] In some specific embodiments, after the first vapor deposition is completed, the process further includes: purging with an inert atmosphere to remove unreacted first metal precursors.
[0039] In some specific embodiments, the first reducing agent includes at least one of a hydrogen-containing gas mixture, dimethylamine borane, and silane.
[0040] In some specific embodiments, the hydrogen-containing gas mixture includes hydrogen and an inert gas.
[0041] In some specific embodiments, the volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%.
[0042] In some specific embodiments, the inert gas includes at least one of nitrogen, argon, helium, and neon.
[0043] In some specific embodiments, the temperature of the first reaction is 120°C to 280°C, and the reaction time is 50s to 70s.
[0044] In some specific embodiments, after the first reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts.
[0045] In some specific embodiments, the temperature of the second vapor deposition is 120°C to 280°C; the deposition time is 3 to 6 seconds; and the deposition pressure is 10... -4 MPa ~ 10 -3 MPa.
[0046] In some specific embodiments, the second carrier gas includes at least one of nitrogen, argon, helium, or neon.
[0047] In some specific embodiments, the second metal precursor includes an organosilver compound and / or an organocopper compound.
[0048] In some specific embodiments, the organosilver compound includes at least one of silver acetylene, silver triethylphosphine, and silver trifluoromethanesulfonate.
[0049] In some specific embodiments, the organocopper compound includes at least one of copper acetylene, dimethyl copper, copper fatty acid, copper succinate, copper dicarboxylate, and copper amino acid.
[0050] In some specific embodiments, after the second vapor deposition is completed, the process further includes: purging with an inert atmosphere to remove unreacted second metal precursors.
[0051] In some specific embodiments, the second reducing agent includes at least one of a hydrogen-containing gas mixture, dimethylamine borane, and silane.
[0052] In some specific embodiments, the hydrogen-containing gas mixture includes hydrogen and an inert gas.
[0053] In some specific embodiments, the volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%.
[0054] In some specific embodiments, the inert gas includes at least one of nitrogen, argon, helium, and neon.
[0055] In some specific embodiments, the temperature of the second reaction is 120°C to 280°C, and the reaction time is 50s to 70s.
[0056] In some specific embodiments, after the second reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts.
[0057] A third aspect of the present invention provides a solid-state battery comprising the composite conductive agent described above or the composite conductive agent prepared according to the preparation method described above.
[0058] In some specific embodiments, the solid-state battery also includes a sulfide solid electrolyte.
[0059] The beneficial technical effects of the present invention through the above technical solution are as follows:
[0060] The composite conductive agent provided by this invention can be applied in solid-state batteries, especially in solid-state batteries containing sulfide solid electrolytes. The composite conductive agent comprises, from the inside out, a conductive agent, a first coating layer, and a second coating layer. The first coating layer includes a first metal, and the second coating layer includes a second metal. The first metal has stronger reducing properties than the second metal. Thus, without affecting electron transport at the positive electrode, by coating the surface of the conductive agent with two metal layers—the inner layer being the first metal coating layer and the outer layer being the second metal coating layer—the stronger reducing properties of the first metal coating layer allow it to preferentially react with the solid electrolyte (such as a sulfide solid electrolyte, Li6PS5Cl) to form a stable interfacial phase (such as MgS or ZnS), inhibiting sulfide decomposition. The outer layer is the second metal coating layer, where the second metal has high conductivity and chemical inertness, ensuring rapid electron transport, while the chemical inertness of the second metal inhibits continuous reaction with the electrolyte. Furthermore, the composite conductive agent significantly inhibits the decomposition of sulfide electrolyte caused by the conductive agent through the different mechanisms of the first and second coating layers, thereby improving the electrochemical performance of the sulfide battery.
[0061] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0062] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0063] Figure 1 The images shown are scanning electron microscope (SEM) images of untreated vapor-grown carbon fibers in Example 2 and composite conductive agent in Example 2, where (a) is untreated vapor-grown carbon fibers in Example 2 and (b) is composite conductive agent in Example 2. Detailed Implementation
[0064] This invention discloses a composite conductive agent, its preparation method, and a solid-state battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0065] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0066] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0067] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.
[0068] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0069] Currently, to achieve the goal of high energy density in sulfide solid electrolytes, it is necessary to maximize the utilization of active materials in the cathode. Adding carbon-based conductive additives can improve the capacity and rate performance of electrode materials. However, carbon-based conductive additives can accelerate capacity loss during cycling and speed up the formation of decomposition products in the solid electrolyte, especially in all-solid-state batteries with high-nickel cathodes matched with sulfide solid electrolytes.
[0070] Therefore, it is necessary to fully consider the characteristics of sulfide solid electrolytes and carbon-based conductive additives, and to improve the degradation of sulfide electrolytes caused by carbon-based conductive additives through modification or coating, thereby reducing long-term capacity decay and improving the overall performance of the battery. Thus, this invention provides a composite conductive agent and its preparation method, as well as a solid-state battery containing this composite conductive additive. The invention will now be described in detail.
[0071] [Composite conductive agent]
[0072] In some embodiments, the present invention provides a composite conductive agent, the composite conductive agent comprising a conductive agent, a first coating layer covering at least a portion of the surface of the conductive agent, and a second coating layer covering at least a portion of the surface of the first coating layer;
[0073] The material of the first cladding layer includes a first metal, and the material of the second cladding layer includes a second metal;
[0074] The reducing power of the first metal is stronger than that of the second metal.
[0075] The provided composite conductive agent has a double-layer coating structure, in which a first coating layer and a second coating layer are sequentially coated on the surface of the conductive agent. The first coating layer is close to the conductive agent and can also be called the inner layer; the second coating layer is far away from the conductive agent and can also be called the outer layer.
[0076] It should be noted that, in this invention, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, the first coating layer coats the conductive agent, which may mean that there are no other structures between the first coating layer and the outer surface of the conductive agent, or that there are one or more other structures between the first coating layer and the outer surface of the conductive agent. Preferably, there are no other structures between the first coating layer and the outer surface of the conductive agent. Similarly, the second coating layer coats the first coating layer, which may mean that there are no other structures between the second coating layer and the outer surface of the first coating layer, or that there are one or more other structures between the second coating layer and the outer surface of the first coating layer. Preferably, there are no other structures between the two outer surfaces of the second coating layer.
[0077] The aforementioned coating layers (first coating layer and second coating layer) are formed or coated on at least a portion of the surface of the core conductive agent, which can protect or improve the core material. They can be used to suppress the decomposition of sulfide electrolytes caused by the conductive agent and improve the electrochemical performance of sulfide all-solid-state batteries. The coating layer being formed or coated on at least a portion of the core surface means that the coating layer can completely encapsulate the core material within the coating layer, or the coating layer can only coat a portion of the outer surface of the core material; that is, the first coating layer can completely coat the core conductive agent, or it can coat a portion of the surface of the core conductive agent, preferably completely; the second coating layer can completely coat the first coating layer, or it can coat a portion of the surface of the first coating layer, preferably completely.
[0078] The composite conductive agent of this invention has a core-shell structure, with a conductive agent as the core and a first metal coating layer and a second metal coating layer sequentially coated on the surface of the conductive agent. That is, the composite conductive agent mainly comprises a conductive agent and a first metal coating layer and a second metal coating layer sequentially coated on the surface of the conductive agent. Without affecting rate performance, it successfully suppresses side reactions between the conductive agent and the solid electrolyte, reduces long-term capacity decay, and improves the overall performance of the all-solid-state battery. Specifically:
[0079] Without affecting electron transport at the positive electrode, two metal layers are coated onto the surface of the conductive agent. The inner layer is a first metal coating layer, and the outer layer is a second metal coating layer. The first metal has stronger reducing power than the second metal. Therefore, the more reducing first metal coating layer preferentially reacts with the solid electrolyte (such as a sulfide solid electrolyte, Li6PS5Cl) to form a stable interfacial phase (such as MgS or ZnS), inhibiting sulfide decomposition. The outer layer is the second metal coating layer, which possesses high conductivity and chemical inertness, ensuring rapid electron transport. Simultaneously, the chemical inertness of the second metal inhibits the continuous reaction with the electrolyte. Thus, through the different mechanisms of the first and second coating layers, the decomposition of sulfide electrolytes caused by the conductive agent is significantly suppressed, improving the electrochemical performance of the sulfide all-solid-state battery.
[0080] The composite conductive agent of this application is suitable for use in batteries containing sulfide solid electrolytes to alleviate problems such as electrolyte decomposition caused by side reactions between existing carbon-based conductive agents and sulfide solid electrolytes.
[0081] In a preferred embodiment of the present invention, the conductive agent in the above-mentioned composite conductive agent can be carbon fiber. A gradient metal coating is deposited on the carbon fiber by atomic layer deposition, which successfully suppresses the decomposition reaction, reduces long-term capacity decay, and improves the overall performance of the all-solid-state battery, thereby alleviating the problem of sulfide electrolyte degradation caused by the current use of carbon additives.
[0082] In some embodiments, the first metal includes, but is not limited to, at least one of Group IIA, Group IIB or Group IIIA metals.
[0083] Preferably, in some embodiments, the first metal includes, but is not limited to, at least one of Mg, Zn, Al, and Ca. Mg, Zn, Al, and Ca are all metals that react with sulfide solid electrolytes to form stable interfacial phases.
[0084] In this invention, the first metal is suitable for reacting with the sulfide solid electrolyte to form a metal sulfide. The selected first metal has strong reducing properties, which can react with the sulfide solid electrolyte to form a stable interfacial phase, suppressing side reactions between the conductive agent and the sulfide, thereby suppressing the decomposition of the sulfide, reducing long-term capacity decay of the battery, and improving the overall performance of the battery.
[0085] In some embodiments, the second metal includes, but is not limited to, at least one of Group IB metals.
[0086] Preferably, in some embodiments, the second metal includes, but is not limited to, Ag and / or Cu. That is, the second metal can be Ag, Cu, or both Ag and Cu. Ag and Cu are both metals with good electrical conductivity and excellent chemical stability.
[0087] In this invention, the second metal has high conductivity, which can ensure rapid electron transport. At the same time, the second metal has a certain degree of chemical inertness (chemical stability), which can further suppress the continuous reaction between the conductive agent and the electrolyte. Combined with the first coating layer, the decomposition of sulfide electrolyte caused by the use of carbon additives is suppressed without affecting the electron transport of the composite cathode, thereby improving the electrochemical performance of the sulfide all-solid-state battery.
[0088] Preferably, in some embodiments, the first coating layer completely covers the surface of the conductive agent.
[0089] Preferably, in some embodiments, the second covering layer completely covers the surface of the first covering layer.
[0090] In this way, by ensuring that the first coating layer completely covers the surface of the conductive agent, and the second coating layer completely covers the surface of the first coating layer, the continuous reaction between the core conductive agent and the electrolyte can be more effectively prevented, the core conductive agent can be more fully and effectively protected, and the roles of the first and second metals can be fully utilized to inhibit the decomposition of the electrolyte and ensure rapid electron transport. Otherwise, if the coating is not complete, the internal metals will react completely with the electrolyte, which will affect the conductivity to some extent.
[0091] In some embodiments, the thickness of the first covering layer is greater than the thickness of the second covering layer.
[0092] In this invention, by controlling the thickness of the first coating layer to be greater than that of the second coating layer, the thinner second coating layer facilitates efficient electron transport, while the thicker first coating layer provides sufficient reactants for the reaction between the first metal and the sulfide solid electrolyte, generating a sufficiently thick and continuous stable interface layer that effectively prevents direct contact between the conductive agent and the electrolyte. In other words, the gradient coating of the metal through different mechanisms significantly suppresses the decomposition of the sulfide electrolyte caused by the use of carbon additives, thereby improving the electrochemical performance of the sulfide all-solid-state battery.
[0093] In some embodiments, the thickness of the first coating layer is 5 nm to 8 nm. As an example, the thickness of the first coating layer can be any one of 5 nm, 5.4 nm, 5.5 nm, 5.8 nm, 6 nm, 6.2 nm, 6.5 nm, 6.8 nm, 7 nm, 7.2 nm, 7.5 nm, 7.8 nm and 8 nm or a range between any two.
[0094] In this invention, by controlling the thickness of the first coating layer within the aforementioned range, sufficient reducing metal atoms can be provided to react with the sulfide electrolyte, generating a continuous and stable interfacial phase and inhibiting sulfide decomposition. If the thickness of the first coating layer is too thin, the reactant material will be rapidly depleted, failing to form a continuous and stable interfacial phase, thus failing to inhibit electrolyte decomposition; if the thickness of the first coating layer is too thick, the generated stable interfacial phase will be too thick, increasing interfacial impedance. That is, by controlling the thickness of the first metal layer within the aforementioned range, while ensuring sufficient reaction between the first metal and the electrolyte to form a stable interfacial phase (such as MgS), the increase in electron transport resistance caused by excessive metal deposition is avoided.
[0095] In some embodiments, the thickness of the second coating layer is 3 nm to 5 nm. As an example, the thickness of the second coating layer can be any one of 3 nm, 3.2 nm, 3.4 nm, 3.5 nm, 3.6 nm, 3.8 nm, 4 nm, 4.2 nm, 4.4 nm, 4.5 nm, 4.6 nm, 4.8 nm, and 5 nm, or a range between any two.
[0096] In this invention, by adjusting the thickness of the second coating layer within the above-mentioned range, it is possible to maintain low resistance while reducing the blockage of the substrate porosity and ensuring dual-channel ion / electron transport.
[0097] In some embodiments, the conductive agent includes, but is not limited to, carbon-based conductive agents.
[0098] In some embodiments, a carbon-based conductive agent includes, but is not limited to, at least one of conductive carbon black, carbon nanotubes, and carbon fibers.
[0099] As an example, the conductive agent can be one or more of Ketjen Black, acetylene black, Super P, carbon nanotubes (CNT), carbon nanofibers (CNF), and vapor-grown carbon fibers (VGCF).
[0100] Preferably, the conductive agent is selected from carbon fiber.
[0101] In some preferred embodiments of the present invention, based on the problem of side reactions between carbon additives (carbon-based conductive agents) and sulfide solid electrolytes, the embodiments of the present invention use atomic layer deposition to gradient deposit a metal coating on conductive carbon additives such as carbon fibers. Without affecting the rate performance, the decomposition reaction is successfully suppressed, long-term capacity decay is reduced, and the overall performance of the all-solid-state battery is improved.
[0102] In some embodiments, the specific surface area of the carbon fiber (such as vapor-grown carbon fiber VGCF) is 15 m². 2 / g~25m 2 / g. As an example, the specific surface area of carbon fiber can be 15m². 2 / g, 16m 2 / g、17m 2 / g、18m 2 / g、19m 2 / g、20m 2 / g、21m 2 / g、22m 2 / g、23m 2 / g、24m 2 / g and 25m 2 Any point value in / g or any range of values between the two.
[0103] Optionally, the specific surface area of Ketjenblack is 1200–1500 m². 2 / g, the specific surface area of acetylene black is 50-70m². 2 / g, the specific surface area of Super P is 40-80m² 2 / g, the specific surface area of CNT is 1800~2500m² 2 / g, the specific surface area of CNF is 100-500m² 2 / g, the specific surface area of VGCF is 15-25m² 2 / g.
[0104] Therefore, this invention, without affecting the electron transport of the composite cathode, employs a gradient metal coating on the surface of the conductive agent. The inner layer is a thick metal coating with strong reducing properties, which preferentially reacts with the sulfide electrolyte (such as Li6PS5Cl) to form a stable interfacial phase (such as MgS, ZnS), inhibiting sulfide decomposition. The outer layer is a thin coating with high conductivity, ensuring rapid electron transport, while its chemical inertness inhibits continuous reaction with the electrolyte. Through different mechanisms of action, the gradient metal coating significantly suppresses the sulfide electrolyte decomposition problem caused by the use of carbon additives, thereby improving the electrochemical performance of the sulfide all-solid-state battery.
[0105] [Preparation method of composite conductive agent]
[0106] In some embodiments, the present invention provides a method for preparing a composite conductive agent, comprising the following steps:
[0107] Using a conductive agent as a substrate, a first metal precursor is deposited on the surface of the conductive agent by atomic layer deposition. A first reducing agent is introduced to react with the first metal precursor to form a first coating layer on the surface of the conductive agent.
[0108] Then, a second metal precursor is deposited on the surface of the first coating layer by atomic layer deposition. A second reducing agent is introduced to react with the second metal precursor to form a second coating layer on the surface of the first coating layer, thus obtaining a composite conductive agent.
[0109] The reducing power of the first metal in the first metal precursor is stronger than that of the second metal in the second metal precursor.
[0110] In this application, atomic layer deposition (ALD) is a technique for depositing materials as single-atom films layer by layer onto a material surface based on a chemical vapor phase. It involves introducing two or more precursor chemicals, each containing different elements of the material to be deposited, onto the material surface one at a time. Each precursor saturates the material surface, forming a monolayer.
[0111] The method for preparing the composite conductive agent provided in this invention uses a conductive agent as a matrix, sequentially introducing a first metal precursor and a second metal precursor, and sequentially depositing the first metal and the second metal on the surface of the conductive agent to obtain the composite conductive agent. This method can gradient-coat a metal layer on the surface of the conductive agent without affecting the electron transport of the composite cathode. The inner layer is a thick metal coating with strong reducing properties, which preferentially reacts with sulfide electrolytes (such as Li6PS5Cl) to form a stable interface phase (such as MgS, ZnS), inhibiting sulfide decomposition. The outer layer is a thin coating with high conductivity, ensuring rapid electron transport, while its chemical inertness inhibits continuous reaction with the electrolyte. Through different mechanisms of action, the gradient coating of metals significantly suppresses the sulfide electrolyte decomposition problem caused by the use of carbon additives, improving the electrochemical performance of sulfide all-solid-state batteries.
[0112] It should be understood that all the features and advantages described above regarding the "composite conductive agent" also apply to the "preparation method of the composite conductive agent," and will not be repeated here.
[0113] In some embodiments, the specific process of forming the first covering layer includes:
[0114] The conductive agent is placed in an atomic layer deposition apparatus, and a first carrier gas and a first metal precursor are introduced to perform a first vapor phase deposition on the surface of the conductive agent. Then, a first reducing agent is introduced to perform a first reaction with the first metal precursor.
[0115] Repeat the above process to form a first coating layer of the target thickness on the surface of the conductive agent.
[0116] In some embodiments, the temperature of the first vapor deposition is 120°C to 280°C; the time of the first vapor deposition is 3s to 6s; and the pressure of the first vapor deposition is 10... -4 MPa ~ 10 -3 MPa. As an example, the temperature of the first vapor deposition can be any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, and 280°C, or a range between any two; the time of the first vapor deposition can be any one of 3s, 4s, 5s, and 6s, or a range between any two; and the pressure of the first deposition can be 10 MPa. -4 MPa, 2×10 -4 MPa, 3×10 -4 MPa, 4×10 -4 MPa, 5×10 -4 MPa, 6×10 -4 MPa, 7×10 -4 MPa, 8×10 -4 MPa, 9×10 -4 MPa and 10 -3 Any point value in MPa or any range value between two of them.
[0117] In some embodiments, the first carrier gas includes, but is not limited to, at least one of nitrogen, argon, helium, or neon.
[0118] In some embodiments, the first metal precursor includes, but is not limited to, one of a magnesium-containing compound, a zinc-containing compound, an aluminum-containing compound, or a calcium-containing compound.
[0119] In some embodiments, the magnesium-containing compound includes, but is not limited to, cyclopentadienyl magnesium and / or methylcyclopentadienyl magnesium. That is, the magnesium-containing compound may include cyclopentadienyl magnesium, may include methylcyclopentadienyl magnesium, or may include both cyclopentadienyl magnesium and methylcyclopentadienyl magnesium.
[0120] In some embodiments, the zinc-containing compound includes, but is not limited to, diethylzinc and / or zinc acetylacetonate. That is, the zinc-containing compound may include diethylzinc, may include zinc acetylacetonate, or may include both diethylzinc and zinc acetylacetonate.
[0121] In some embodiments, an aluminum-containing compound, including but not limited to at least one of trimethylaluminum, isobutylaluminum, triethylaluminum, or aluminum chloride.
[0122] In some embodiments, the calcium-containing compound includes, but is not limited to, cyclopentadienyl calcium and / or tert-butoxy calcium. That is, the calcium-containing compound may include cyclopentadienyl calcium, may include tert-butoxy calcium, or may include both cyclopentadienyl calcium and tert-butoxy calcium.
[0123] In addition, in other embodiments, the magnesium-containing compound, zinc-containing compound, aluminum-containing compound, and calcium-containing compound are not limited to the above-listed types. Other types of magnesium-containing compounds, zinc-containing compounds, aluminum-containing compounds, and calcium-containing compounds may be used as long as they can be used to coat the conductive agent with a first metal. These will not be described in detail here.
[0124] In some embodiments, after the first vapor deposition is completed, the method further includes: purging with an inert atmosphere to remove unreacted first metal precursors.
[0125] In some embodiments, the first reducing agent includes, but is not limited to, at least one of a hydrogen-containing gas mixture, dimethylamine borane, and silane.
[0126] In some embodiments, the mixture contains hydrogen, including but not limited to hydrogen and an inert gas.
[0127] In some embodiments, the volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%. As an example, the volume content of hydrogen in the mixed atmosphere of hydrogen and inert gas can be any one of 5%, 6%, 7%, 8%, 9%, and 10%, or a range between any two.
[0128] In some embodiments, an inert gas, including but not limited to at least one of nitrogen, argon, helium, and neon.
[0129] In some embodiments, the temperature of the first reaction is 120°C to 280°C, and the time of the first reaction is 50s to 70s. As an example, the temperature of the first reaction can be any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, and 280°C, or a range between any two. The time of the first reaction can be any one of 50s, 52s, 54s, 55s, 56s, 58s, 60s, 62s, 64s, 65s, 68s, and 70s, or a range between any two.
[0130] In some embodiments, after the first reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts.
[0131] In some embodiments, the inert atmosphere introduced after the first reaction is completed includes, but is not limited to, at least one of nitrogen, argon, helium and neon.
[0132] As an example, the specific process of forming the first coating layer includes:
[0133] The conductive agent is placed in the reaction chamber of the atomic layer deposition apparatus. The temperature of the reaction chamber is raised to 120–280°C and maintained. The reaction chamber is then sealed and the pressure is reduced to 10°C. -4 MPa ~ 10 -3 The reaction chamber is subjected to a first carrier gas, such as nitrogen, and a first metal precursor, such as cyclopentadienyl magnesium, at a pressure of MPa. The first vapor deposition is carried out for 3 to 6 seconds, and then an inert gas is introduced to remove the unreacted first metal precursor. The temperature in the reaction chamber is 120 to 280°C. Then, a first reducing agent (such as a hydrogen-argon mixture with a hydrogen volume content of 5% to 10%) is introduced to carry out the reaction for 50 to 70 seconds. After the reaction is completed, an inert gas (such as nitrogen) is introduced to remove the unreacted first metal precursor and reaction byproducts.
[0134] Repeat the above process to form a first coating layer of the target thickness on the surface of the conductive agent.
[0135] In some embodiments, the specific process of forming the second covering layer includes:
[0136] A second carrier gas and a second metal precursor are introduced into an atomic layer deposition apparatus, and a second vapor phase deposition is performed on the surface of a conductive agent coated with a first coating layer. Then, a second reducing agent is introduced to react with the second metal precursor in a second reaction.
[0137] Repeat the above process to form a second coating layer of the target thickness on the surface of the first coating layer.
[0138] In some embodiments, the temperature of the second vapor deposition is 120°C to 280°C; the deposition time is 3 to 6 seconds; and the deposition pressure is 10... -4 MPa ~ 10 -3 MPa. As an example, the temperature for the second vapor deposition can be any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, and 280°C, or a range between any two. The time for the second vapor deposition can be any one of 3s, 4s, 5s, and 6s, or a range between any two. The pressure for the second deposition can be 10 MPa. -4 MPa, 2×10 -4 MPa, 3×10 -4 MPa, 4×10 -4 MPa, 5×10 -4 MPa, 6×10 -4 MPa, 7×10 -4 MPa, 8×10 -4 MPa, 9×10 -4 MPa and 10 -3 Any point value in MPa or any range value between two of them.
[0139] In some embodiments, the second carrier gas includes, but is not limited to, at least one of nitrogen, argon, helium, or neon.
[0140] In some embodiments, the second metal precursor includes, but is not limited to, organosilver compounds and / or organocopper compounds. That is, the second metal precursor may include organosilver compounds, may include organocopper compounds, or may include both organosilver compounds and organocopper compounds.
[0141] In some embodiments, an organosilver compound includes, but is not limited to, at least one of silver acetylene, silver triethylphosphine, and silver trifluoromethanesulfonate.
[0142] In some embodiments, the organocopper compound includes, but is not limited to, at least one of copper acetylene, dimethyl copper, copper fatty acid, copper succinate, copper dicarboxylate, and copper amino acid.
[0143] In addition, in other embodiments, the organosilver compounds and organocopper compounds are not limited to the types listed above. Other types of organosilver compounds and organocopper compounds may be used as long as they can be used to coat the conductive agent with a second metal. These will not be described in detail here.
[0144] In some embodiments, after the second vapor deposition is completed, the method further includes: purging with an inert atmosphere to remove unreacted second metal precursors.
[0145] In some embodiments, the second reducing agent includes, but is not limited to, at least one of a hydrogen-containing gas mixture, dimethylamine borane, and silane.
[0146] In some embodiments, the mixture contains hydrogen, including but not limited to hydrogen and an inert gas.
[0147] In some embodiments, the volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%. As an example, the volume content of hydrogen in the mixture of hydrogen and inert gas can be any one of 5%, 6%, 7%, 8%, 9%, and 10%, or a range between any two.
[0148] In some embodiments, an inert gas, including but not limited to at least one of nitrogen, argon, helium, and neon.
[0149] In some embodiments, the temperature of the second reaction is 120°C to 280°C, and the time of the second reaction is 50s to 70s. As an example, the temperature of the second reaction can be any one of 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, and 280°C, or a range between any two. The time of the second reaction can be any one of 55s, 52s, 54s, 55s, 56s, 58s, 60s, 62s, 64s, 65s, 68s, and 70s, or a range between any two.
[0150] In some embodiments, after the second reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts.
[0151] In some embodiments, the inert atmosphere introduced after the second reaction is completed includes, but is not limited to, at least one of nitrogen, argon, helium and neon.
[0152] As an example, the specific process of forming the second coating layer includes:
[0153] After the first coating layer is deposited, maintain the temperature of the reaction chamber at 120–280°C and hold. Then, seal the reaction chamber and depressurize it to 10°C. -4 MPa ~ 10 -3 At a pressure of MPa, a second carrier gas, such as nitrogen, and a second metal precursor, such as triethylphosphine silver, are introduced into the reaction chamber for second vapor deposition for 3 to 6 seconds. Then, an inert gas is introduced to remove unreacted second metal precursors. The temperature in the reaction chamber is 120 to 280°C. Then, a second reducing agent (such as a hydrogen-argon mixture with a hydrogen volume content of 5% to 10%) is introduced to react for 50 to 70 seconds. After the reaction is completed, an inert gas (such as nitrogen) is introduced to remove unreacted second metal precursors and reaction byproducts.
[0154] Repeat the above process to form a second coating layer of the target thickness on the surface of the first coating layer.
[0155] Solid-state batteries
[0156] In some embodiments, a solid-state battery is provided, comprising the composite conductive agent described above or the composite conductive agent prepared according to the preparation method described above.
[0157] In some specific embodiments, the solid-state battery also includes a sulfide solid electrolyte.
[0158] In some embodiments, the solid-state battery further includes a positive electrode, a negative electrode, and a first solid electrolyte.
[0159] In some embodiments, the positive electrode sheet includes a positive electrode material, a second solid electrolyte, and a composite conductive agent.
[0160] In some embodiments, the mass ratio of the positive electrode material, the second solid electrolyte, and the composite conductive agent is (70–90):(9–29):(1–5). As an example, the mass ratio of the positive electrode material, the second solid electrolyte, and the composite conductive agent can be 70:29:1, 70:25:5, 75:23:2, 80:17:3, 85:11:4, 90:9:1, etc.
[0161] In some embodiments, the cathode material includes at least one of lithium niobate-coated 6-series nickel-cobalt-manganese ternary materials, lithium niobate-coated 8-series nickel-cobalt-manganese ternary materials, and lithium niobate-coated 9-series nickel-cobalt-manganese ternary materials. All of the above-mentioned ternary cathode materials are commercially available cathode materials.
[0162] In some embodiments, the particle size Dv50 of the cathode material is 4 μm to 8 μm.
[0163] In some embodiments, the second solid electrolyte includes Li 6-x PS 5-x Cl 1+x Li 6-x PS 5-x ClBr x and Li 3+ x Ge x P 1-x At least one of S4, wherein 0 ≤ x ≤ 0.5.
[0164] In some embodiments, the particle size Dv50 of the second solid electrolyte is 0.5 μm to 1.5 μm.
[0165] In some embodiments, the ionic conductivity of the second solid electrolyte is ≥5 mS / cm.
[0166] In some embodiments, the negative electrode includes a Li-In negative electrode.
[0167] In some embodiments, the mass content of Li is 1% to 5% based on the total mass of the Li-In negative electrode.
[0168] In some embodiments, the thickness of the negative electrode sheet is 50 μm to 100 μm.
[0169] In some embodiments, the first solid electrolyte includes Li 6-x PS 5-x Cl 1+x Li 6-x PS 5-x ClBr x and Li 3+ x Ge x P 1-x At least one of S4, wherein 0 ≤ x ≤ 0.5.
[0170] In some embodiments, the particle size Dv50 of the first solid electrolyte is 10 μm to 20 μm.
[0171] In some embodiments, the ionic conductivity of the first solid electrolyte is ≥10 ms / cm.
[0172] In some embodiments, the assembly of a solid-state battery includes:
[0173] (1) Weigh 150mg of the first solid electrolyte and spread it evenly in the battery mold. Press it into an electrolyte sheet using 350Mpa and hold the pressure for 3min.
[0174] (2) Mix the positive electrode material, the second solid electrolyte and the composite conductive agent, disperse them and spread them evenly on one side of the electrolyte sheet, pressurize with 200 MPa and hold the pressure for 3 minutes;
[0175] (3) Place the 10mm diameter Li-In negative electrode sheet on the other side of the electrolyte sheet, put in the copper foil current collector, pressurize with 150Mpa pressure and hold for 3min;
[0176] (4) Tighten the mold and place it inside the pressure mold shell. Use a torque wrench to pressurize the mold to 50 MPa.
[0177] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0178] Example 1
[0179] The preparation of the composite conductive agent includes the following steps:
[0180] (1) A surface area of 20m² 2 / g of vapor-grown carbon fiber (VGCF) was placed in an atomic layer deposition reaction bottle, which was then placed in a chamber. The temperature of the reaction chamber was raised to 180°C and a vacuum was drawn to 10°C. -4 Using nitrogen as the carrier gas, a precursor cyclopentadienyl magnesium was introduced into the reaction chamber for 0.5 s, followed by a 4 s vapor deposition reaction. Then, nitrogen was introduced to purge for 100 s to remove unreacted cyclopentadienyl magnesium from the reaction chamber. Next, a hydrogen-argon mixture with a hydrogen volume content of 10% was introduced for 1 s, followed by a 60 s reaction. Then, nitrogen was introduced to purge for 80 s to remove unreacted gases and reaction byproducts from the reaction chamber. This process was repeated 15 times to obtain Mg@VGCF with a magnesium coating thickness of 5.6 nm.
[0181] (2) Place Mg@VGCF into an atomic layer deposition reaction bottle, place the reaction bottle into the chamber, raise the temperature of the reaction chamber to 180°C and evacuate to 10°C. -4 At a pressure of MPa, using nitrogen as the carrier gas, the precursor copper acetylacetonate was introduced into the reaction chamber for 0.5 s, followed by vapor deposition for 4 s. Then, nitrogen was purged for 100 s to remove unreacted copper acetylacetonate from the reaction chamber. Next, a hydrogen-argon mixture with a hydrogen volume content of 10% was introduced for 1 s, and the reaction proceeded for 60 s. Nitrogen was then purged for 80 s to remove unreacted gases and reaction byproducts. This process was repeated 9 times to obtain Cu@Mg@VGCF with a copper coating thickness of 3.2 nm.
[0182] Example 2
[0183] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0184] In step (1), the precursor cyclopentadienyl magnesium is replaced with diethylzinc, and the hydrogen-argon mixture with a hydrogen volume content of 10% is replaced with dimethylamineborane.
[0185] In step (2), the precursor copper acetylacetone is replaced with triethylphosphine silver, and the hydrogen-argon mixture with a hydrogen volume content of 10% is replaced with dimethylamine borane.
[0186] Everything else is the same as in Example 1.
[0187] Example 3
[0188] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0189] In step (1), the precursor cyclopentadienylmagnesium is replaced with trimethylaluminum, and the hydrogen-argon mixture with a hydrogen volume content of 10% is replaced with silane.
[0190] In step (2), the precursor copper acetylacetone is replaced with triethylphosphine silver, and the hydrogen-argon mixture with a hydrogen volume content of 10% is replaced with silane.
[0191] Everything else is the same as in Example 1.
[0192] Example 4
[0193] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0194] In step (1), the vapor-grown carbon fiber is replaced with conductive carbon black.
[0195] Everything else is the same as in Example 1.
[0196] Example 5
[0197] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0198] In step (1), the precursor cyclopentadienyl magnesium is replaced with cyclopentadienyl calcium.
[0199] Everything else is the same as in Example 1.
[0200] Example 6
[0201] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0202] In step (1), the thickness of the magnesium coating layer is 7 nm;
[0203] In step (2), the copper cladding layer has a thickness of 4 nm.
[0204] Everything else is the same as in Example 1.
[0205] Example 7
[0206] The preparation method of the composite conductive agent differs from that in Example 1 in that:
[0207] In step (1), the thickness of the magnesium coating layer is 8 nm;
[0208] In step (2), the copper cladding layer has a thickness of 5 nm.
[0209] Everything else is the same as in Example 1.
[0210] Comparative Example 1
[0211] The composite conductive agent used is an untreated material with a specific surface area of 20 m². 2 / g of vapor-grown carbon fibers.
[0212] Comparative Example 2
[0213] The preparation of the composite conductive agent differs from that in Example 1 in that:
[0214] Step (2) was not performed, i.e. the composite conductive agent is Mg@VGCF with a magnesium coating thickness of 5.6 nm.
[0215] Everything else is the same as in Example 1.
[0216] Comparative Example 3
[0217] The preparation of the composite conductive agent differs from that in Example 1 in that:
[0218] Step (1) was not performed, i.e. the composite conductive agent is Cu@VGCF with a copper coating thickness of 3.2 nm.
[0219] Everything else is the same as in Example 1.
[0220] Comparative Example 4
[0221] The preparation of the composite conductive agent differs from that in Example 1 in that:
[0222] In Cu@Mg@VGCF, the magnesium coating thickness is 3.2 nm and the copper coating thickness is 5.6 nm.
[0223] Everything else is the same as in Example 1.
[0224] Comparative Example 5
[0225] The preparation of the composite conductive agent differs from that in Example 1 in that:
[0226] Step (1) was not performed, and the thickness of the copper coating layer was 1 nm, that is, the composite conductive agent was Cu@VGCF with a copper coating layer thickness of 1 nm.
[0227] Everything else is the same as in Example 1.
[0228] Comparative Example 6
[0229] The preparation of the composite conductive agent differs from that in Example 1 in that:
[0230] Step (1) was not performed, and the thickness of the copper coating layer was 8 nm, that is, the composite conductive agent was Cu@VGCF with a copper coating layer thickness of 8 nm.
[0231] Everything else is the same as in Example 1.
[0232] Assembly and performance testing of solid electrolytes
[0233] 1. Assembly of solid electrolytes:
[0234] LiNbO2@LiNi coated with lithium niobate 0.83 Co 0.12 Mn 0.5 O2 ternary cathode material (particle size Dv50 of 6.5 μm), Li6PS5Cl (particle size Dv50 of 0.8 μm), and the composite conductive agent prepared in the examples and comparative examples were ground in an agate mortar at a mass ratio of 80:15:5 for 30 min to obtain a solid cathode composite material. The anode was a Li-In alloy with a thickness of 100 μm and a Li mass fraction of 1%, cut into 10 mm diameter discs. 150 mg of Li6PS5Cl (particle size Dv50 of 15 μm) was weighed and evenly spread in a battery mold, and pressurized at 350 MPa to form an electrolyte sheet, holding the pressure for 3 min. The composite cathode powder was evenly spread on one side of the electrolyte sheet, and pressurized at 200 MPa for 3 min. A 10 mm diameter disc was then formed. The Li-In sheet is placed on the other side of the electrolyte sheet, and a copper foil current collector is placed in it. The pressure is increased to 150 MPa and held for 3 minutes. The mold is tightened and the glove box is removed. The mold is placed in the pressurized mold shell and the mold is pressurized to 50 MPa with a torque wrench to obtain a solid-state battery.
[0235] 2. Performance Testing
[0236] Charge-discharge tests were conducted using a constant current charge-discharge mode. Test items included: the first charge-discharge capacity and initial coulombic efficiency of the solid-state battery at a current density of 0.1C, the discharge capacity at 0.3C, 0.5C, and 1C, and the capacity retention rate after 100 charge-discharge cycles at a current density of 0.5C. Specifically, after two charge-discharge cycles at a current density of 0.1C, the solid-state battery was subsequently subjected to two charge-discharge cycles at 0.3C, 0.5C, and 1C rates respectively. The first charge-discharge capacity and initial coulombic efficiency at 0.1C were recorded, where initial coulombic efficiency = first discharge capacity / first charge capacity, and the first discharge capacity at 0.3C, 0.5C, and 1C were recorded. After the above rate test was completed, 100 charge-discharge cycles were performed continuously at a 0.5C rate (charging cut-off voltage 3.65V, discharging cut-off voltage 2.0V). The capacity retention rate was calculated as: Capacity retention rate = Discharge capacity on the 100th cycle / Discharge capacity on the 1st cycle. The discharge cut-off voltage was 2.0V, and the charging cut-off voltage was 3.65V.
[0237] The test results are shown in Table 1.
[0238] Table 1
[0239]
[0240] As shown in Table 1, under the same main material type, the solid-state batteries assembled using the conductive carbon additive modified with the gradient metal coating provided by this invention in Examples 1-7 exhibited better initial coulombic efficiency and cycle stability in Examples 1-7. Comparative Example 1 used an unmodified conductive additive material, whose discharge capacity and initial efficiency were lower than those in Examples 1-7, and its capacity retention was only 84.2%, indicating that the unmodified conductive carbon material is prone to side reactions with the sulfide electrolyte. Comparative Example 2 used a conductive carbon additive material Mg@VGCF with only one layer of metal deposited; this material exhibited excellent cycle stability, but its rate performance was poor. Comparative Example 3 used a conductive carbon additive material Cu@VGCF with only one layer of metal deposited; this material exhibited good rate performance, but its cycle stability was poor. Comparative Example 4 used a conductive carbon additive material Cu@Mg@VGCF with a thin inner and thick outer metal layer deposited; the rate performance and cycle stability of this material were slightly improved, but its overall performance was inferior to that of Examples 1-7. Comparative Example 5, with a Cu@VGCF conductive carbon additive with a thickness of 1 nm, showed no significant change in initial efficiency, but the capacity retention of the solid-state battery was slightly improved. This indicates that the coating layer was too thin, and side reactions still existed. Comparative Example 6, with a Cu@VGCF conductive carbon additive with a thickness of 8 nm, showed a more significant improvement in the initial efficiency and capacity retention of the battery, but it was slightly worse than Examples 1-7. This was mainly because the excessively thick coating layer affected the electron transport capability of the conductive carbon additive, thereby affecting the initial efficiency and cycle stability of the material.
[0241] Scanning electron microscope (SEM) images of the untreated vapor-grown carbon fibers in Example 2 and the composite conductive agent in Example 2 are shown below. Figure 1 As shown, Figure 1 In example (a), the untreated vapor-grown carbon fiber is shown. Figure 1 (b) is the composite conductive agent in Example 2. (From...) Figure 1 As can be seen from the SEM image of VGCF without a metal coating, the surface is relatively smooth. After the conductive additive surface is coated with a metal atomic layer, the surface becomes rougher.
[0242] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0243] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0244] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0245] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0246] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid-state battery, characterized in that, It includes a composite conductive agent and a sulfide solid electrolyte, wherein the composite conductive agent includes a carbon-based conductive agent, a first coating layer covering at least a portion of the surface of the conductive agent, and a second coating layer covering at least a portion of the surface of the first coating layer; The material of the first coating layer includes a first metal, and the material of the second coating layer includes a second metal; The reducing power of the first metal is stronger than that of the second metal.
2. The solid-state battery according to claim 1, characterized in that, The first metal includes at least one metal from Group IIA, Group IIB, or Group IIIA; And / or, the second metal includes at least one of Group IB metals.
3. The solid-state battery according to claim 2, characterized in that, The first metal includes at least one of Mg, Zn, Al, and Ca; And / or, the second metal includes Ag and / or Cu.
4. The solid-state battery according to claim 1, characterized in that, The first coating layer completely covers the surface of the conductive agent; And / or, the second covering layer completely covers the surface of the first covering layer.
5. The solid-state battery according to any one of claims 1 to 4, characterized in that, The composite conductive agent satisfies at least one of the following technical features (1) to (3): (1) The thickness of the first coating layer is greater than the thickness of the second coating layer; (2) The thickness of the first coating layer is 5 nm to 8 nm; (3) The thickness of the second coating layer is 3nm~5nm.
6. The solid-state battery according to claim 5, characterized in that, The carbon-based conductive agent includes at least one of conductive carbon black, carbon nanotubes, and carbon fibers. The specific surface area of the carbon fiber is 15m². 2 / g~25m 2 / g.
7. A method for preparing a composite conductive agent in a solid-state battery as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Using a conductive agent as a substrate, a first metal precursor is deposited on the surface of the conductive agent by atomic layer deposition. A first reducing agent is introduced to react with the first metal precursor to form a first coating layer on the surface of the conductive agent. Then, a second metal precursor is deposited on the surface of the first coating layer by atomic layer deposition. A second reducing agent is introduced to react with the second metal precursor to form a second coating layer on the surface of the first coating layer, thereby obtaining the composite conductive agent. The reducing power of the first metal in the first metal precursor is stronger than that of the second metal in the second metal precursor.
8. The method for preparing the composite conductive agent according to claim 7, characterized in that, The specific process for forming the first coating layer includes: The conductive agent is placed in an atomic layer deposition apparatus, and a first carrier gas and a first metal precursor are introduced to perform a first vapor phase deposition on the surface of the conductive agent. Then, a first reducing agent is introduced to perform a first reaction with the first metal precursor. Repeat the above process to form a first coating layer of the target thickness on the surface of the conductive agent; And / or, the specific process of forming the second coating layer includes: A second carrier gas and a second metal precursor are introduced into an atomic layer deposition apparatus to perform a second vapor phase deposition on the surface of the conductive agent coated with a first coating layer. Then, a second reducing agent is introduced to react with the second metal precursor in a second reaction. Repeat the above process to form a second coating layer of the target thickness on the surface of the first coating layer.
9. The method for preparing the composite conductive agent according to claim 8, characterized in that, The preparation method satisfies at least one of the following technical features (1) to (14): (1) The temperature of the first vapor deposition is 120℃~280℃; the time of the first vapor deposition is 3s~6s; the pressure of the first vapor deposition is 10 -4 MPa~10 -3 MPa; (2) The first carrier gas includes at least one of nitrogen, argon, helium or neon; (3) The first metal precursor includes one of magnesium-containing compounds, zinc-containing compounds, aluminum-containing compounds, or calcium-containing compounds; The magnesium-containing compound includes cyclopentadienyl magnesium and / or methylcyclopentadienyl magnesium; The zinc-containing compounds include diethylzinc and / or zinc acetylacetonate; The aluminum-containing compound includes at least one of trimethylaluminum, isobutylaluminum, triethylaluminum, or aluminum chloride; The calcium-containing compound includes cyclopentadienyl calcium and / or tert-butoxy calcium; (4) After the first vapor deposition is completed, the process further includes: purging with an inert atmosphere to remove unreacted first metal precursor; (5) The first reducing agent includes at least one of a mixed gas containing hydrogen, dimethylamine borane, and silane; The hydrogen-containing gas mixture includes hydrogen and an inert gas; The volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%. The inert gas includes at least one of nitrogen, argon, helium, and neon; (6) The temperature of the first reaction is 120℃~280℃, and the time of the first reaction is 50s~70s; (7) After the first reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts; (8) The temperature of the second vapor deposition is 120℃~280℃; the time of the second vapor deposition is 3~6s; the pressure of the second vapor deposition is 10 -4 MPa~10 -3 MPa; (9) The second carrier gas includes at least one of nitrogen, argon, helium or neon; (10) The second metal precursor comprises an organosilver compound and / or an organocopper compound; The organosilver compound includes at least one of silver acetylene, silver triethylphosphine, and silver trifluoromethanesulfonate. The organocopper compounds include at least one of copper acetylene, dimethyl copper, copper fatty acid, copper succinate, copper dicarboxylic acid, and copper amino acid. (11) After the second vapor deposition is completed, the process further includes: purging with an inert atmosphere to remove unreacted second metal precursor; (12) The second reducing agent includes at least one of a mixed gas containing hydrogen, dimethylamine borane, and silane; The hydrogen-containing gas mixture includes hydrogen and an inert gas; The volume content of hydrogen in the mixture of hydrogen and inert gas is 5% to 10%. The inert gas includes at least one of nitrogen, argon, helium, and neon; (13) The temperature of the second reaction is 120℃~280℃, and the time of the second reaction is 50s~70s; (14) After the second reaction is completed, the process further includes: purging with an inert atmosphere to remove unreacted gases and reaction byproducts.
Citation Information
Patent Citations
Continuous carbon nanotube fiber reinforced copper-based composite material as well as preparation method and application thereof
CN115142008A
Double-layer metal coated and modified metal lithium negative electrode material and preparation method thereof
CN116504948A